2019
DOI: 10.5194/acp-19-11743-2019
|View full text |Cite
|
Sign up to set email alerts
|

EARLINET evaluation of the CATS Level 2 aerosol backscatter coefficient product

Abstract: Abstract. We present the evaluation activity of the European Aerosol Research Lidar Network (EARLINET) for the quantitative assessment of the Level 2 aerosol backscatter coefficient product derived by the Cloud-Aerosol Transport System (CATS) aboard the International Space Station (ISS; Rodier et al., 2015). The study employs correlative CATS and EARLINET backscatter measurements within a 50 km distance between the ground station and the ISS overpass and as close in time as possible, typically with the startin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 95 publications
(139 reference statements)
0
22
0
Order By: Relevance
“…The results shown in this paper are critical to understanding the uncertainties in CATS 1064 nm Level 2 data products, as the calibration uncertainties from backscatter lidars generally impose a lower bound on the uncertainties in cloud/aerosol extinction and optical depth retrievals from such instruments (Young et al, 2013(Young et al, , 2016. To date, the CATS cloud and aerosol top/base heights have been used for various applications, including volcanic plume transport (Hughes et al, 2016), above-cloud aerosol properties (Rajapakshe et al, 2017), pyrocumulonimbus smoke heights (Christian et al, 2019), and cloud diurnal variability (Noel et al, 2018). More recently, CATS cloud and aerosol optical properties (e.g., extinction, optical depth, ice water content) from Level 2 V-3.00 data have been compared to EARLINET aerosol products (Proestakis et al, 2019), used to estimate thin cirrus radiative forcing (Dolinar et al, 2019), and demonstrated the diurnal variability of aerosol properties (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The results shown in this paper are critical to understanding the uncertainties in CATS 1064 nm Level 2 data products, as the calibration uncertainties from backscatter lidars generally impose a lower bound on the uncertainties in cloud/aerosol extinction and optical depth retrievals from such instruments (Young et al, 2013(Young et al, , 2016. To date, the CATS cloud and aerosol top/base heights have been used for various applications, including volcanic plume transport (Hughes et al, 2016), above-cloud aerosol properties (Rajapakshe et al, 2017), pyrocumulonimbus smoke heights (Christian et al, 2019), and cloud diurnal variability (Noel et al, 2018). More recently, CATS cloud and aerosol optical properties (e.g., extinction, optical depth, ice water content) from Level 2 V-3.00 data have been compared to EARLINET aerosol products (Proestakis et al, 2019), used to estimate thin cirrus radiative forcing (Dolinar et al, 2019), and demonstrated the diurnal variability of aerosol properties (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…where α par is the particulate extinction and z s is the CATS altitude. The particulate backscatter was computed from the Polly XT 1064 and 607 nm signals through the methodology described in Proestakis et al (2019). The uncertainty in the backscatter coefficient retrieval is estimated to be between 5 % and 20 % (Ansmann et al, 1992;Whiteman et al, 2003;Povey et al, 2014).…”
Section: Ground-based Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schaap et al, 2009;Stachlewska et al, 2017bStachlewska et al, , 2018, and PM 1 (e.g. Qin et al, 2018) concentrations can improve our knowledge of the atmospheric environment.…”
Section: Introductionmentioning
confidence: 99%